Remains of the everyday : a century of recycling in Beijing - Goldstein, Joshua, 1965- (University of California Press, 2021)
"Remains of the Everyday traces the changing material culture and industrial ecology of China through the lens of recycling. Over the last century, waste recovery and secondhand goods markets have been integral to Beijing's economic functioning and cultural identity, and acts of recycling have figured centrally in the ideological imagination of modernity and citizenship. On the one hand, the Chinese state has repeatedly promoted acts of voluntary recycling as exemplary of conscientious citizenship. On the other, informal recycling networks-from the night soil carriers of the Republican era to the collectors of plastic and cardboard in Beijing's neighborhoods today-have been represented as undisciplined, polluting, and technologically primitive due to the municipal government's failure to control them. The result, Joshua Goldstein argues, is the repeatedly re-inscribed exclusion of waste workers from formations of modern urban citizenship as well as the intrinsic liminality of recycling itself as an economic process"--